Composite hard carbon material, preparation method thereof, negative electrode and sodium ion battery

CN122950481APending Publication Date: 2026-10-20JIANGSU PYLON BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610754256.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-28
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

颗粒硬度高、易辊压破碎:硬碳颗粒的机械强度高但韧性差,在极片辊压过程中容易发生颗粒破碎,导致电极结构破坏、循环性能下降

Benefits of technology

本发明实施例提供的复合硬碳材料,以纳米纤维素形成三维骨架,其具有良好的成膜性和网络状粘接特性,应用到负极片中,与常规的粘结剂体系(例如CMC/SBR体系)相容性好,可提高极片剥离强度,同时相较于常规粘接剂体系也可减少常规粘结剂用量。在三维骨架中负载适量的导电剂,改善纳米纤维素不导电的问题。三维骨架无明显氧化还原行为,电化学惰性良好,其自身不参与电化学储钠反应,从而避免了因额外引入储钠位点导致的电压曲线变化或首次库仑效率下降;同时,纳米纤维素骨架的多孔结构为钠离子提供快速传输通道,并缓冲硬碳颗粒的体积膨胀。由纳米纤维素交织成的三维骨架具有柔性,且纳米纤维素的单纤维和单纤维之间通过醚键交联使得三维骨架有较佳的结构稳定性,柔性+结构稳定性使得复合硬碳材料在辊压过程中不易破碎。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention relates to the field of battery materials technology, and discloses a composite hard carbon material, its preparation method, a negative electrode, and a sodium-ion battery. The composite hard carbon material includes modified particles, each comprising hard carbon particles and a three-dimensional network shell coating the surface of the hard carbon particles. The three-dimensional network shell includes a three-dimensional framework and a conductive agent loaded on the three-dimensional framework. The three-dimensional framework is formed by interwoven nanofibers of cellulose, with the individual fibers of the nanofibers cross-linked by ether bonds. In the composite hard carbon material, the mass ratio of the three-dimensional framework to the hard carbon particles is 0.08~0.25:1, and the mass ratio of the conductive agent to the three-dimensional framework is 0.1~0.17:1. When applied to a negative electrode, this composite hard carbon material can improve the peel strength of the negative electrode, buffer expansion, provide more sodium deposition sites and sodium storage space, and improve the capacity and lifespan of the sodium-ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery materials technology, and more specifically, to composite hard carbon materials and their preparation methods, negative electrodes, and sodium-ion batteries. Background Technology

[0002] Hard carbon materials are considered one of the most promising anode materials for sodium-ion batteries due to their abundant resources, low cost, and high sodium storage capacity. However, hard carbon anodes face the following technical challenges in practical applications: High particle hardness and easy to be crushed by rolling: Hard carbon particles have high mechanical strength but poor toughness. They are prone to breakage during the rolling process of the electrode sheet, which leads to damage to the electrode structure and a decrease in cycle performance.

[0003] Granulation and pelletizing are difficult: Hard carbon precursors are mostly biomass, which makes it difficult to prepare spherical particles through conventional processes, affecting the compaction density and processing performance of the electrode sheets.

[0004] Complex surface functional groups and poor adhesion: The surface of hard carbon contains abundant oxygen-containing functional groups, which have poor compatibility with conventional binders, resulting in low electrode peel strength and easy powder shedding.

[0005] Traditional coating methods are limited: Existing technologies mostly use carbon sources such as asphalt and resin to coat and modify hard carbon, but these methods not only involve a large number of existing patent barriers, but the coating layer is also prone to shrinkage and cracking during heat treatment, making it difficult to form a uniform and firm coating layer.

[0006] In view of this, the present invention is proposed. Summary of the Invention

[0007] The purpose of this invention is to provide composite hard carbon materials and their preparation methods, negative electrodes, and sodium-ion batteries, aiming to improve at least one of the problems mentioned in the background art.

[0008] This invention is implemented as follows: In a first aspect, the present invention provides a composite hard carbon material, comprising modified particles, wherein the modified particles include hard carbon particles and a three-dimensional network shell coating the surface of the hard carbon particles. The three-dimensional network shell includes a three-dimensional framework and a conductive agent loaded on the three-dimensional framework. The three-dimensional framework is formed by interwoven nanocellulose, and the single fibers of nanocellulose are cross-linked by ether bonds. In composite hard carbon materials, the mass ratio of the three-dimensional framework to hard carbon particles is 0.08~0.25:1, and the mass ratio of the conductive agent to the three-dimensional framework is 0.1~0.17:1.

[0009] In an optional embodiment, the conductive agent is selected from at least one of carbon nanotubes and graphene.

[0010] In an optional embodiment, the Dv50 of the hard carbon particles in the composite hard carbon material is 3~6μm; And / or, in composite hard carbon materials, the particle size of the conductive agent is 10 nm to 5 μm; And / or, in composite hard carbon materials, the length of a single cellulose nanofiber is 500~3000nm and the diameter is 4~20nm.

[0011] In an optional embodiment, a sodium supplement is also loaded onto the three-dimensional skeleton; Optionally, the sodium supplement is selected from at least one of sodium oxalate and sodium carbonate; Optionally, in the composite hard carbon material, the mass ratio of sodium supplement to hard carbon particles is 5~15:100.

[0012] In a second aspect, the present invention provides a method for preparing a composite hard carbon material as described in any of the foregoing embodiments, comprising: A mixed slurry is provided, in which hard carbon particles, nanocellulose and conductive agents are dispersed; The mixed slurry is spray-dried to obtain the initial product; The initial product was placed in an inert atmosphere and subjected to low-temperature heat treatment at 200~350℃ to cause dehydration and etherification crosslinking between the single fibers of nanocellulose, thus obtaining a composite hard carbon material.

[0013] In an optional embodiment, the method for preparing the mixed slurry includes: Hard carbon powder, water, and dispersant are mixed and dispersed evenly to obtain a hard carbon suspension; Nanocellulose, water, and a conductive agent are mixed and dispersed evenly to obtain a nanocellulose dispersion; The hard carbon suspension and the nanocellulose dispersion were mixed evenly to obtain a mixed slurry. Optionally, the hard carbon powder, water, and dispersant are mixed and dispersed uniformly by means of ultrasonic dispersion combined with mechanical stirring; Optionally, the mass ratio of dispersant to hard carbon powder is 0.1~0.3:100; Optionally, the hard carbon suspension and the nanocellulose dispersion are mixed uniformly by high-speed shearing or ultrasonic dispersion; Optionally, the dispersant is a nonionic dispersant; optionally, the nonionic dispersant is selected from at least one of polyethylene glycol and polyvinylpyrrolidone.

[0014] In an optional implementation, at least one of the following features (1) to (4) is included: (1) During the spray drying process, the inlet temperature is 150~200℃ and the outlet temperature is 80~100℃; (2) The low-temperature heat treatment time is 1~4h; (3) The low-temperature treatment process involves heating to 200-350℃ at a heating rate of 2-5℃ / min; (4) The inert atmosphere is nitrogen or argon.

[0015] Thirdly, the present invention provides a negative electrode, comprising a current collector and a negative electrode active layer, wherein the negative electrode active layer comprises a composite hard carbon material as described in any of the foregoing embodiments.

[0016] In an optional embodiment, the compaction density of the negative electrode active layer is 0.90~1.00 g / cm³; Optionally, the compaction density of the negative electrode active layer is 0.90~0.98 g / cm³. Optionally, the compaction density of the negative electrode active layer is 0.90~0.95 g / cm³; Optionally, the compaction density of the negative electrode active layer is 0.95~1.00 g / cm³; Optionally, the negative electrode active layer comprises a composite hard carbon material, sodium carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 94~97:1.5~3.0:1.5~3.0.

[0017] Fourthly, the present invention provides a sodium-ion battery, including a negative electrode as described in the foregoing embodiments.

[0018] The present invention has the following beneficial effects: The composite hard carbon material provided in this invention uses nanocellulose to form a three-dimensional framework, which has good film-forming properties and network-like adhesion characteristics. When applied to negative electrode sheets, it exhibits good compatibility with conventional binder systems (such as CMC / SBR systems), improving electrode peel strength and reducing the amount of conventional binder used compared to conventional binder systems. Loading an appropriate amount of conductive agent into the three-dimensional framework mitigates the non-conductive nature of nanocellulose. The three-dimensional framework exhibits no significant redox behavior and good electrochemical inertness, not participating in the electrochemical sodium storage reaction, thus avoiding voltage curve changes or initial coulombic efficiency decreases caused by the introduction of additional sodium storage sites. Simultaneously, the porous structure of the nanocellulose framework provides a rapid transport channel for sodium ions and buffers the volume expansion of hard carbon particles. The three-dimensional framework, interwoven with nanocellulose, is flexible, and the cross-linking between nanocellulose fibers via ether bonds gives the three-dimensional framework excellent structural stability. This combination of flexibility and structural stability makes the composite hard carbon material less prone to breakage during rolling. Detailed Implementation

[0019] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0020] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0021] The present invention provides a composite hard carbon material, comprising modified particles, wherein the modified particles include hard carbon particles and a three-dimensional network shell coating the surface of the hard carbon particles. The three-dimensional network shell includes a three-dimensional framework and a conductive agent loaded on the three-dimensional framework. The three-dimensional framework is formed by interwoven nanocellulose, and the single fibers of nanocellulose are cross-linked by ether bonds. In composite hard carbon materials, the mass ratio of the three-dimensional framework to hard carbon particles is 0.08 to 0.25:1 (e.g., 0.08:1, 0.1:1, 0.15:1, 0.2:1 or 0.25:1), and the mass ratio of the conductive agent to the three-dimensional framework is 0.1 to 0.17:1 (e.g., 0.1:1, 0.12:1, 0.15:1 or 0.17:1).

[0022] The composite hard carbon material provided in this invention uses nanocellulose to form a three-dimensional framework, which has good film-forming properties and network-like adhesion characteristics. When applied to negative electrode sheets, it exhibits good compatibility with conventional binder systems (such as CMC / SBR systems), improving electrode peel strength and reducing the amount of conventional binder used compared to conventional binder systems. Loading an appropriate amount of conductive agent into the three-dimensional framework mitigates the non-conductive nature of nanocellulose. The three-dimensional framework exhibits no significant redox behavior and good electrochemical inertness, not participating in the electrochemical sodium storage reaction, thus avoiding voltage curve changes or initial coulombic efficiency decreases caused by the introduction of additional sodium storage sites. Simultaneously, the porous structure of the nanocellulose framework provides a rapid transport channel for sodium ions and buffers the volume expansion of hard carbon particles. The three-dimensional framework, interwoven with nanocellulose, is flexible, and the cross-linking between nanocellulose fibers via ether bonds gives the three-dimensional framework excellent structural stability. This combination of flexibility and structural stability makes the composite hard carbon material less prone to breakage during rolling.

[0023] Furthermore, the three-dimensional framework loaded with conductive agent of this invention synergistically forms a sodium deposition guiding network with hard carbon particles. Depending on the compaction density, the sodium storage mechanism exhibits differentiated characteristics of "coexistence and dominance": In a conventional compaction density system (0.95~1.00 g / cm³), the electrode is fully compacted, and the three-dimensional skeleton of carbon nanofibers mainly plays a role in flexible buffering and thickening. The embedding-filling of hard carbon particles is the dominant mechanism for sodium storage, and the three-dimensional skeleton loaded with conductive agent assists in providing a conductive network and some deposition sites. In systems with few negative electrodes or low compaction (0.90~0.95 g / cm³), the three-dimensional framework loaded with conductive agents retains more original pore space. The defect sites on the surface of hard carbon particles serve as preferential nucleation centers for sodium. The three-dimensional framework loaded with conductive agents provides a three-dimensional electron transport channel with a high specific surface area, guiding sodium ions to be uniformly deposited on the surface of the framework and in the pores during charging, forming sodium deposition behavior. At this time, space-deposited sodium storage and hard carbon embedded sodium storage jointly dominate the capacity contribution.

[0024] Therefore, the composite hard carbon material provided by this invention, when applied to the negative electrode, can improve the peel strength of the negative electrode, buffer expansion, provide more sodium deposition sites and sodium storage space to the negative electrode, and improve the capacity and lifespan of sodium-ion batteries.

[0025] It should be noted that the amount of nanocellulose coating should not be excessive. An overly thick coating layer will block sodium ion transport channels, increase the overall electrode impedance, and reduce the electrode compaction density and volumetric capacity. Similarly, the amount of conductive agent loading should not be excessive, as this can easily lead to powder agglomeration, significantly increasing the viscosity of the negative electrode slurry, increasing the difficulty of coating processing, and also reducing the sodium storage active space, thus raising raw material costs. When the amounts of nanocellulose and conductive agent are within the limits specified in this invention, better electrochemical performance can be ensured when the composite hard carbon material is applied to the negative electrode.

[0026] Optionally, the conductive agent is selected from at least one of carbon nanotubes and graphene.

[0027] Optionally, in order to enable the composite hard carbon material to have better electrochemical performance when applied to the negative electrode, the Dv50 of the hard carbon particles in the composite hard carbon material is 3~6μm (e.g., 3μm, 4μm, 5μm or 6μm).

[0028] Optionally, in order to improve the electrochemical performance of the composite hard carbon material when applied to the negative electrode, the particle size of the conductive agent in the composite hard carbon material is 10 nm to 5 μm. Optionally, in the composite hard carbon material, the single fiber length of the nanocellulose is 500~3000nm (e.g., 500nm, 1000nm, 1500nm, 2000nm, 2500nm or 3000nm, or any two of the above values), and the diameter is 4~20nm (e.g., 4nm, 6nm, 8nm, 10nm, 16nm or 20nm, or any two of the above values). Fibers of this length and diameter ensure better stability of the formed three-dimensional framework.

[0029] Optionally, the three-dimensional skeleton is also loaded with a sodium supplement.

[0030] Optionally, the sodium supplement is selected from at least one of sodium oxalate and sodium carbonate.

[0031] Optionally, in the composite hard carbon material, the mass ratio of sodium supplement to hard carbon particles is 5 to 15:100 (e.g., 5:100, 10:100 or 15:100).

[0032] The sodium supplement is stable in aqueous slurries, reaching a positive electrode potential of 3.6~3.9 V (vs Na) during the initial charging. + When sodium ions are released from the decomposition of sodium (Na), they compensate for the irreversible capacity loss caused by the formation of the SEI.

[0033] The present invention provides a method for preparing a composite hard carbon material, comprising: A mixed slurry is provided, in which hard carbon particles, nanocellulose and conductive agents are dispersed; The mixed slurry is spray-dried to obtain the initial product; The initial product is placed in an inert atmosphere and subjected to low-temperature heat treatment at 200~350℃ (e.g., 200℃, 250℃, 300℃ or 350℃) to cause dehydration and etherification crosslinking between the single fibers of nanocellulose, thus obtaining a composite hard carbon material.

[0034] The preparation method provided in this invention first coats hard carbon particles through spray drying, followed by low-temperature heat treatment to cause dehydration and etherification crosslinking of nanocellulose, improving crystallinity and significantly reducing its swelling rate in carbonate electrolyte, thus ensuring the structural stability of the electrode during long-term cycling. Furthermore, this method eliminates the need for modification of the hard carbon particles themselves, the use of traditional coating materials such as asphalt and resin, and high-temperature carbonization of nanocellulose, thereby obtaining a composite negative electrode material with high breakage resistance, high sphericity, high peel strength, and good conductivity.

[0035] The composite hard carbon material provided in this invention can be obtained by the preparation method provided in this embodiment.

[0036] Specifically, the preparation method is as follows: S1. Preparation of a mixed slurry for spray drying. (1) Hard carbon powder, deionized water and dispersant are ultrasonically dispersed and mechanically stirred to obtain a uniformly dispersed hard carbon suspension.

[0037] Optionally, the dispersant is a nonionic dispersant; preferably, it is at least one of polyethylene glycol (PEG) and polyvinylpyrrolidone (PVP).

[0038] These nonionic dispersants are completely decomposed and removed during the subsequent low-temperature heat treatment process, avoiding adverse effects on electrolyte decomposition and SEI film formation.

[0039] The addition of dispersant in this step ensures that the hard carbon particles are uniformly dispersed in the suspension, and also ensures that the components are uniformly dispersed after the nanocellulose dispersion is mixed with the suspension in this step.

[0040] Optionally, the mass ratio of hard carbon powder in the hard carbon suspension is 10-15% (e.g., 10%, 12% or 15%), and the mass ratio of dispersant to hard carbon particles is 0.1-0.3:100 (e.g., 0.1:100, 0.2:100 or 0.3:100).

[0041] The Dv50 of hard carbon powder is 3~6μm (e.g., 3μm, 4μm, 5μm or 6μm). Hard carbon powder with this particle size can ensure the preparation of modified hard carbon anode materials with better electrochemical performance.

[0042] (2) Nanocellulose, deionized water and conductive agent are dispersed evenly by high-speed shearing or ultrasonication to obtain nanocellulose dispersion.

[0043] Optionally, the solid content of the nanocellulose dispersion is 12-18% (e.g., 12%, 15% or 18%).

[0044] A uniform interpenetrating network is formed by high-speed shearing or ultrasonic dispersion, and after drying, conductive modified nanocellulose is obtained with an electrical conductivity ≥10. - ³ S / cm.

[0045] The nanocellulose single fibers have a length of 500–3000 nm and a diameter of 4–20 nm. The conductive agent has a particle size of 10 nm–5 μm. The nanocellulose of the above dimensions and the conductive agent can ensure the formation of a stable coating layer on the surface of hard carbon particles, and ensure that the conductive agent can be stably loaded on the three-dimensional framework formed by the nanocellulose.

[0046] (3) Mix and stir the hard carbon suspension and nanocellulose dispersion to make them evenly dispersed to obtain a mixed slurry of hard carbon particles, nanocellulose and conductive agent.

[0047] Optionally, when the three-dimensional framework of the composite hard carbon material to be prepared is loaded with a sodium supplement, the sodium supplement can be added during the preparation of the hard carbon suspension, the preparation of the nanocellulose dispersion, or the mixing of the two.

[0048] S2, Spray drying The spray drying equipment is set with an inlet temperature of 150~200℃ (e.g., 150℃, 180℃ or 200℃) and an outlet temperature of 80~100℃ (e.g., 80℃, 90℃ or 100℃) to spray dry the mixed slurry and obtain the initial product.

[0049] S3, Low-temperature heat treatment The initial sample is placed in an inert atmosphere and heated to 200-350°C (e.g., 200°C, 250°C, 300°C, or 350°C) at a heating rate of 2-5°C / min (e.g., 2°C / min, 3°C / min, 4°C / min, or 5°C / min) for 1-4 hours (e.g., 1 hour, 2 hours, 3 hours, or 4 hours) and then allowed to cool naturally.

[0050] In this step, the low-temperature treatment causes the nanocellulose to undergo dehydration and etherification cross-linking, which improves its crystallinity and significantly reduces its swelling rate in the carbonate electrolyte, thus ensuring the structural stability of the electrode during long-term cycling.

[0051] It should be noted that the heat treatment temperature should be within the range defined in this invention. If the temperature is too low, dehydration and etherification crosslinking cannot be achieved, the fiber has poor resistance to electrolyte swelling, and the electrode deformation is severe in the later stages of cycling. If the temperature is too high, the ether bond crosslinking structure between nanocellulose will be destroyed, which will lead to carbonization of nanocellulose, causing nanocellulose to lose its flexibility. This makes the material prone to brittle fracture and spatial structure collapse during the rolling process, unable to provide the ability to buffer stress, and also difficult to maintain a stable sodium deposition interface.

[0052] Setting the heating rate to 2~5℃ / min in this step ensures uniform heating of the fiber and simultaneous cross-linking reaction, forming a uniform and stable three-dimensional network skeleton.

[0053] Optionally, the inert atmosphere is nitrogen or argon.

[0054] This invention provides a negative electrode, including a current collector and a negative electrode active layer, wherein the negative electrode active layer includes the composite hard carbon material provided in this invention.

[0055] Optionally, the compaction density of the negative electrode active layer is 0.90~1.00 g / cm³. Within this compaction density range, the negative electrode exhibits good electrochemical performance.

[0056] Optionally, the compaction density of the negative electrode active layer is 0.90~0.98 g / cm³.

[0057] Optionally, the compaction density of the negative electrode active layer is 0.90~0.95 g / cm³. This compaction density range is suitable for low-density negative electrode systems where sodium deposition is required to dominate. Low-pressure roller compaction is used to ensure that the framework pore structure is not damaged, providing a stable three-dimensional space for sodium deposition.

[0058] Optionally, the compaction density of the negative electrode active layer is 0.95~1.00 g / cm³. This compaction density is a conventional compaction density, achieved using a conventional rolling process.

[0059] Furthermore, the negative electrode active layer comprises a composite hard carbon material, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in a mass ratio of 94~97:1.5~3.0:1.5~3.0. This ratio of negative electrode active layer imparts better electrochemical performance to the battery.

[0060] This invention provides a sodium-ion battery, including a negative electrode provided in this invention. Because this battery includes the negative electrode provided in this invention, it exhibits superior electrochemical performance.

[0061] Example 1 100g of hard carbon powder, 660g of deionized water, 10g of sodium supplement (sodium oxalate), and 0.2g of dispersant (PEG) were ultrasonically dispersed and mechanically stirred to obtain a uniformly dispersed hard carbon suspension. The hard carbon powder had a D50 of 5μm and the mass ratio of hard carbon powder in the suspension was 13%. 15g of nanocellulose (Guilin Qihong Technology, CNF-cp99, length 1~3 micrometers, diameter 4~10nm), 114g of deionized water and 2.1g of conductive agent (carbon nanotubes, particle size 10~30 nm) were uniformly dispersed by high-speed shearing or ultrasonication to obtain a nanocellulose dispersion with a solid content of 15%. The hard carbon suspension and the nanocellulose dispersion were mixed evenly according to the mass ratio of nanocellulose to hard carbon powder of 0.15:1 to obtain a mixed slurry.

[0062] The spray drying equipment is set with an inlet temperature of 180℃ and an outlet temperature of 90℃ to spray dry the mixed slurry and obtain the initial product.

[0063] The initial sample was placed in an inert atmosphere and heated to 280℃ at a heating rate of 3℃ / min for 2 hours to obtain the modified hard carbon anode material.

[0064] The modified hard carbon anode material obtained includes modified particles, which include hard carbon particles and a three-dimensional network shell coating the surface of the hard carbon particles. The three-dimensional network shell includes a three-dimensional framework and a conductive agent loaded on the three-dimensional framework. The three-dimensional framework is formed by interwoven nanocellulose, and the single fibers of nanocellulose are cross-linked by ether bonds. In the composite hard carbon material, the mass ratio of the three-dimensional framework to the hard carbon particles is 0.15:1, and the mass ratio of the conductive agent to the three-dimensional framework is 0.14:1.

[0065] The modified hard carbon anode material of this embodiment includes hard carbon particles and a three-dimensional network shell coating the surface of the hard carbon particles. The three-dimensional network shell includes a three-dimensional framework and a conductive agent loaded on the three-dimensional framework.

[0066] Example 2 100g of hard carbon powder, 885g of deionized water, 15g of sodium supplement (sodium carbonate), and 0.1g of dispersant (PVP) were ultrasonically dispersed and mechanically stirred to obtain a uniformly dispersed hard carbon suspension. The hard carbon powder had a D50 of 5μm and the mass ratio of hard carbon powder in the suspension was 10%. 8g of nanocellulose (Guilin Qihong Technology, CNF-cp99, length 1~3 micrometers, diameter 4~10nm), 73g of deionized water and 0.8g of conductive agent (carbon nanotubes, particle size 10~30 nm) were uniformly dispersed by high-speed shearing or ultrasonication to obtain a nanocellulose dispersion with a solid content of 12%. The hard carbon suspension and the nanocellulose dispersion were mixed evenly according to the mass ratio of nanocellulose to hard carbon powder of 0.08:1 to obtain a mixed slurry.

[0067] The spray drying equipment is set with an inlet temperature of 150℃ and an outlet temperature of 80℃ to spray dry the mixed slurry and obtain the initial product.

[0068] The initial sample was placed in an inert atmosphere and heated to 200℃ at a heating rate of 2℃ / min for 4 hours to obtain the modified hard carbon anode material.

[0069] The modified hard carbon anode material obtained includes modified particles, which include hard carbon particles and a three-dimensional network shell coating the surface of the hard carbon particles. The three-dimensional network shell includes a three-dimensional framework and a conductive agent loaded on the three-dimensional framework. The three-dimensional framework is formed by interwoven nanocellulose, and the single fibers of nanocellulose are cross-linked by ether bonds. In the composite hard carbon material, the mass ratio of the three-dimensional framework to the hard carbon particles is 0.08:1, and the mass ratio of the conductive agent to the three-dimensional framework is 0.1:1.

[0070] Example 3 100g of hard carbon powder, 562g of deionized water, 5g of sodium supplement (sodium oxalate), and 0.3g of dispersant (PVP) were ultrasonically dispersed and mechanically stirred to obtain a uniformly dispersed hard carbon suspension. The hard carbon powder had a D50 of 5μm and the mass ratio of hard carbon powder in the suspension was 15%. 25g of nanocellulose (Guilin Qihong Technology, CNF-cp99, length 1~3 micrometers, diameter 4~10nm), 162g of deionized water and 4.25g of conductive agent (carbon nanotubes, particle size 10~30 nm) were uniformly dispersed by high-speed shearing or ultrasonication to obtain a nanocellulose dispersion with a solid content of 18%. The hard carbon suspension and the nanocellulose dispersion were mixed evenly according to the mass ratio of nanocellulose to hard carbon powder of 0.25:1 to obtain a mixed slurry.

[0071] The spray drying equipment is set with an inlet temperature of 200℃ and an outlet temperature of 100℃ to spray dry the mixed slurry and obtain the initial product.

[0072] The initial sample was placed in an inert atmosphere and heated to 350℃ for 1 hour at a heating rate of 5℃ / min to obtain the modified hard carbon anode material.

[0073] The modified hard carbon anode material obtained includes modified particles, which include hard carbon particles and a three-dimensional network shell coating the surface of the hard carbon particles. The three-dimensional network shell includes a three-dimensional framework and a conductive agent loaded on the three-dimensional framework. The three-dimensional framework is formed by interwoven nanocellulose, and the single fibers of nanocellulose are cross-linked by ether bonds. In the composite hard carbon material, the mass ratio of the three-dimensional framework to the hard carbon particles is 0.25:1, and the mass ratio of the conductive agent to the three-dimensional framework is 0.17:1.

[0074] Example 4 This embodiment is basically the same as Embodiment 1, except that: Sodium oxalate was not added to the hard carbon suspension.

[0075] Example 5 This embodiment is basically the same as Embodiment 1, except that the heating rate of the low-temperature heat treatment process is 10℃ / min.

[0076] Comparative Example 1 This comparative example is basically the same as Example 1, except that: this comparative example provides the hard carbon powder from Example 1 without any treatment.

[0077] Comparative Example 2 This comparative example is basically the same as Example 1, except that: the product is spray-dried directly with hard carbon suspension and then subjected to low-temperature heat treatment.

[0078] Comparative Example 3 This comparative example is basically the same as Example 1, except that no conductive agent was added to the nanocellulose dispersion.

[0079] Comparative Example 4 This comparative example is basically the same as Example 1, except that no nanocellulose was added to the nanocellulose dispersion.

[0080] Comparative Example 5 This comparative example is basically the same as Example 1, except that the amount of nanocellulose added to the nanocellulose dispersion is too large, and the mass ratio of nanocellulose to hard carbon is 0.30:1, that is, 30g of nanocellulose is added.

[0081] Comparative Example 6 This comparative example is basically the same as Example 1, except that the amount of conductive agent added to the nanocellulose dispersion is too large, at 1.5g.

[0082] Comparative Example 7 This comparative example is basically the same as Example 1, except that the low-temperature heat treatment temperature is 180°C.

[0083] Comparative Example 8 This comparative example is basically the same as Example 1, except that the low-temperature heat treatment temperature is 380°C.

[0084] Comparative Example 9 This comparative example is basically the same as Example 1, except that: no low-temperature heat treatment is performed after spray drying.

[0085] Experimental Example The composite hard carbon materials prepared in the various embodiments and comparative examples were used to make negative electrode sheets, wherein the current collector was copper foil, and the negative electrode active layer included composite hard carbon materials, CMC and SBR in a mass ratio of 95:3:2, with a compaction density of 0.96 g / cm³. A positive electrode is provided, wherein the current collector of the positive electrode is aluminum foil, and its active layer includes NFPP active material, conductive carbon black and PVDF binder in a mass ratio of 95:2:3; An electrolyte is provided, comprising 1 mol / L NaPF6, EC to DMC volume ratio of 1:1, and 5% FEC film-forming additive.

[0086] A 2Ah sodium-ion battery was assembled from negative electrode, positive electrode and electrolyte. Its electrochemical performance was measured. The specific test method was to perform the first activation charge and discharge at 0.1C current and the long cycle test at 0.5C room temperature. The initial coulombic efficiency, reversible specific capacity, capacity retention rate after 1000 cycles and electrode peel strength were tested. The specific test method was the industry-standard sodium-ion battery electrochemical test method.

[0087] Record the test results in Table 1.

[0088] Table 1 Test results for each embodiment and comparative example

[0089] As can be seen from Table 1, the composite hard carbon materials prepared in each embodiment of the present invention, when used as negative electrode sheets in batteries, can give the batteries better electrochemical performance. The electrochemical performance of each embodiment is significantly better than that of Comparative Example 1, indicating that forming a three-dimensional skeleton with a conductive agent loaded on the surface of conventional hard carbon particles can significantly improve the electrochemical performance of the material.

[0090] Comparing Example 4 with Example 1, Example 4 has a lower initial coulombic efficiency and a larger irreversible capacity, indicating that adding sodium supplement in Example 1 is beneficial to improving the initial coulombic efficiency of the battery. Comparing Example 5 with Example 1, Example 5 showed a faster capacity decay rate during long cycles, indicating that if the heating rate of the low-temperature heat treatment is too fast during the preparation process, the uneven heating inside and outside the fiber, the inconsistent degree of crosslinking, and the uneven density of the skeleton structure will make it difficult to achieve a higher level of electrochemical performance. Comparing Comparative Example 2 with Example 1, Comparative Example 2 has weak anti-expansion ability and poor rate performance, indicating that the absence of a three-dimensional skeleton loaded with conductive agent on the surface of hard carbon particles makes it impossible to improve the structural stability and dynamic performance of hard carbon materials. Comparing Comparative Example 3 with Example 1, the high-rate discharge polarization of Comparative Example 3 was severe, indicating that the conductive agent was not loaded on the three-dimensional framework. Since nanocellulose is non-conductive, the conductivity of the electrode will be deteriorated. Comparing Comparative Example 4 with Example 1, Comparative Example 4 has insufficient sodium storage space and extremely poor structural stability, indicating that without the addition of nanocellulose during spray drying, a three-dimensional skeleton cannot be formed on the surface of hard carbon particles, and the overall performance of the material cannot be improved. Comparing Comparative Example 5 with Example 1, the ion conduction of Comparative Example 5 was blocked and the kinetic performance deteriorated, indicating that if too much nanocellulose is added, the electrochemical performance will be reduced due to the excessive thickness of the coating layer crowding out the ion channels. Comparing Comparative Example 6 with Example 1, the slurry of Comparative Example 6 had poor processability and the effective sodium storage capacity was diluted, indicating that excessive use of nanocellulose would crowd out the active sodium storage sites. Comparing Comparative Example 7 with Example 1, the electrode of Comparative Example 7 is prone to expansion and warping in the later stage of cycling, indicating that the low temperature of the low-temperature heat treatment process will cause insufficient fiber cross-linking and insufficient resistance to electrolyte swelling. Comparing Comparative Example 8 with Example 1, the skeleton of Comparative Example 8 lost its flexibility and the particles were easily pulverized and broken, indicating that the heat treatment temperature was too high, which damaged the ether bond structure and lost the buffering expansion effect. Comparing Comparative Example 9 with Example 1, the electrode of Comparative Example 9 is prone to powder shedding and has a significantly shortened cycle life, indicating that if low-temperature heat treatment is not performed, the fibers will only be physically wrapped without chemical bonding, and the skeleton will be very easy to collapse.

[0091] In summary, the composite hard carbon material provided in this invention, when applied to the negative electrode, can impart better electrochemical performance to the battery. Compared with existing technologies, the composite hard carbon material and its preparation method provided by this invention have the following characteristics and advantages: 1. A three-dimensional flexible framework is constructed using conductive-modified nanocellulose, into which hard carbon particles are embedded. During the rolling process, the flexible framework absorbs stress through deformation, protecting the integrity of the particles. Industrially mature spray drying technology is employed to prepare spherical composite particles with controllable particle size; the process is continuous, low-cost, and suitable for large-scale production.

[0092] 2. The nanocellulose framework exhibits excellent film-forming properties and network-like adhesive characteristics. A binder system combining nanocellulose and CMC / SBR can improve electrode peel strength while reducing the amount of conventional binder compared to a pure CMC / SBR system. Modification of the nanocellulose with conductive agents imparts excellent electronic conductivity to the framework, solving the insulation problems inherent in traditional cellulose.

[0093] 3. Within the normal operating potential range of sodium-ion batteries, the nanocellulose framework, after low-temperature heat treatment, exhibits no significant redox behavior and good electrochemical inertness. It does not participate in the electrochemical sodium storage reaction, thus avoiding voltage curve changes or initial coulombic efficiency decreases caused by the introduction of additional sodium storage sites. Simultaneously, the porous structure of the nanocellulose framework provides a rapid transport channel for sodium ions and buffers the volume expansion of hard carbon particles.

[0094] 4. Low-temperature heat treatment causes dehydration and etherification crosslinking of nanocellulose, increasing its crystallinity and significantly reducing its swelling rate in carbonate electrolyte, ensuring the structural stability of the electrode during long-term cycling. It is compatible with sodium supplementation systems, allowing the direct addition of water-stable sodium supplementers such as sodium oxalate or sodium carbonate to the slurry before spray drying, achieving uniform distribution of the sodium supplementer and improving the initial coulombic efficiency. The technical solution provided by this invention does not alter the internal structure of hard carbon; it only composites through physical intercalation, achieving a hard carbon mass ratio as high as 80%~95%, thus resulting in minimal specific capacity loss in the composite material.

[0095] 5. The conductive agent-loaded nanocellulose three-dimensional framework of the present invention synergistically forms a sodium deposition guiding network with hard carbon particles. Depending on the compaction density, the sodium storage mechanism exhibits differentiated characteristics of "coexistence and dominance": In conventional compaction density systems (0.95-1.00 g / cm³), the electrode sheets are fully compacted, and the nanocellulose skeleton mainly plays a role in flexible buffering and thickening. The embedding-filling of hard carbon particles is the dominant mechanism for sodium storage, while the conductive agent-loaded nanocellulose skeleton assists in providing a conductive network and some deposition sites.

[0096] In systems with few negative electrodes or low-pressure compaction (0.90-0.95 g / cm³), the nanocellulose framework retains more original pore space, and the defect sites on the surface of hard carbon particles serve as preferential nucleation centers for sodium. The nanocellulose conductive framework doped with carbon nanotubes or graphene provides a three-dimensional electron transport channel with a high specific surface area, guiding sodium ions to be uniformly deposited on the surface and in the pores of the framework during charging, forming sodium deposition behavior. At this time, spatially deposited sodium storage and hard carbon embedded sodium storage jointly dominate the capacity contribution.

[0097] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A composite hard carbon material, characterized in that, It includes modified particles, which include hard carbon particles and a three-dimensional network shell coating the surface of the hard carbon particles; The three-dimensional network shell includes a three-dimensional skeleton and a conductive agent loaded on the three-dimensional skeleton. The three-dimensional skeleton is formed by interwoven nanocellulose fibers, and the single fibers of nanocellulose are cross-linked by ether bonds. In the composite hard carbon material, the mass ratio of the three-dimensional skeleton to the hard carbon particles is 0.08~0.25:1, and the mass ratio of the conductive agent to the three-dimensional skeleton is 0.1~0.17:

1.

2. The composite hard carbon material according to claim 1, characterized in that, The conductive agent is selected from at least one of carbon nanotubes and graphene.

3. The composite hard carbon material according to claim 1, characterized in that, In the composite hard carbon material, the Dv50 of the hard carbon particles is 3~6μm; And / or, in the composite hard carbon material, the particle size of the conductive agent is 10 nm to 5 μm; And / or, in the composite hard carbon material, the single fiber length of the nanocellulose is 500~3000nm and the diameter is 4~20nm.

4. The composite hard carbon material according to claim 1, characterized in that, The three-dimensional skeleton is also loaded with a sodium supplement; Optionally, the sodium supplement is selected from at least one of sodium oxalate and sodium carbonate; Optionally, in the composite hard carbon material, the mass ratio of the sodium supplement to the hard carbon particles is 5~15:

100.

5. A method for preparing a composite hard carbon material as described in any one of claims 1 to 4, characterized in that, include: A mixed slurry is provided, wherein the hard carbon particles, the nanocellulose, and the conductive agent are dispersed in the mixed slurry; The mixed slurry was spray-dried to obtain the initial product; The initial product was placed in an inert atmosphere and subjected to low-temperature heat treatment at 200~350℃ to cause dehydration and etherification crosslinking between the single fibers of the nanocellulose, thus obtaining the composite hard carbon material.

6. The preparation method according to claim 5, characterized in that, The method for preparing the mixed slurry includes: Hard carbon powder, water, and dispersant are mixed and dispersed evenly to obtain a hard carbon suspension; The nanocellulose, water, and conductive agent are mixed and dispersed evenly to obtain a nanocellulose dispersion. The hard carbon suspension and the nanocellulose dispersion are mixed evenly to obtain the mixed slurry; Optionally, the hard carbon powder, water, and dispersant are mixed and dispersed uniformly by means of ultrasonic dispersion combined with mechanical stirring; Optionally, the mass ratio of the dispersant to the hard carbon powder is 0.1~0.3:100; Optionally, the hard carbon suspension and the nanocellulose dispersion are mixed uniformly by high-speed shearing or ultrasonic dispersion; Optionally, the dispersant is a nonionic dispersant; optionally, the nonionic dispersant is selected from at least one of polyethylene glycol and polyvinylpyrrolidone.

7. The preparation method according to claim 5, characterized in that, Includes at least one of the following features (1) to (4): (1) During the spray drying process, the inlet temperature is 150~200℃ and the outlet temperature is 80~100℃; (2) The low-temperature heat treatment time is 1~4h; (3) The low-temperature treatment process involves heating to 200-350℃ at a heating rate of 2-5℃ / min; (4) The inert atmosphere is nitrogen or argon.

8. A negative electrode, characterized in that, It includes a current collector and a negative electrode active layer, wherein the negative electrode active layer includes the composite hard carbon material as described in any one of claims 1 to 4.

9. The negative electrode according to claim 8, characterized in that, The compaction density of the negative electrode active layer is 0.90~1.00 g / cm³; Optionally, the compaction density of the negative electrode active layer is 0.90~0.98 g / cm³; Optionally, the compaction density of the negative electrode active layer is 0.90~0.95 g / cm³; Optionally, the compaction density of the negative electrode active layer is 0.95~1.00 g / cm³; Optionally, the negative electrode active layer comprises the composite hard carbon material, sodium carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 94~97:1.5~3.0:1.5~3.

0.

10. A sodium-ion battery, characterized in that, Includes the negative electrode as described in claim 8 or 9.